INTERFERENCE BETWEEN LEGAL AND MEDICAL ISSUES IN THE FIELD OF PALLIATIVE CARE SERVICES - Burz, Claudia Cristina; Apan, Rodica Diana (International Journal of Legal and Social Order, 2021)
The population of a country benefits from prevention, curative programs but also from palliative programs, addressed to patients with chronic diseases. Palliative care is defined as a holistic, complex approach to patients with chronic diseases, in order to increase the quality of life of patients and their families. From a legislative point of view, since 2018, all aspects of palliative care have been regulated in Romania as well. As can be seen from the present study, the regulation of palliative services is a complex, far-reaching one, regarding the providers of palliative services and the ways of carrying out their activity, as well as the patients. Beneficiaries of these services and the interdisciplinary team involved in their provision. We find through this study that this regulation is a combination of the legal field with elements of medical activity. During the Conference "Public safety and the need for high social capital", panel VII, "Protection of human capital in the field of the right to health and social care" was organized, and this study aims to raise the protection of human capital through palliative services, analyzing the stage and content of their regulation at national level.